Association of dissolved mercury with dissolved organic carbon in U.S. rivers and streams: The role of watershed soil organic carbon. Issue 4 (21st April 2016) - Stoken, Olivia M.; Riscassi, Ami L.; Scanlon, Todd M.
Abstract: Streams and rivers are important pathways for the export of atmospherically deposited mercury (Hg) from watersheds. Dissolved Hg (HgD ) is strongly associated with dissolved organic carbon (DOC) in stream water, but the ratio of HgD to DOC is highly variable between watersheds. In this study, the HgD :DOC ratios from 19 watersheds were evaluated with respect to Hg wet deposition and watershed soil organic carbon (SOC) content. On a subset of sites where data were available, DOC quality measured by specific ultra violet absorbance at 254 nm, was considered as an additional factor that may influence HgD :DOC . No significant relationship was found between Hg wet deposition and HgD :DOC, but SOC content (g m −2 ) was able to explain 81% of the variance in the HgD :DOC ratio (ng mg −1 ) following the form: HgD :DOC=17.8*SOC −0.41 . The inclusion of DOC quality as a secondary predictor variable explained only an additional 1% of the variance. A mathematical framework to interpret the observed power‐law relationship between HgD :DOC and SOC suggests Hg supply limitation for adsorption to soils with relatively large carbon pools. With SOC as a primary factor controlling the association of HgD with DOC, SOC data sets may be utilized to predict stream HgD :DOC ratios on a more geographically widespread basis. In watersheds where DOC data are available, estimates of HgD may be readily obtained. Future Hg emissions policies must consider soil‐mediated processes that affect the transport of Hg and DOC from terrestrial watersheds to streams for accurate predictions of water quality impacts. Key Points: Watershed soil organic carbon is a primary control on Hg and DOC in streams Large‐scale soil carbon data sets can be used to predict stream Hg:DOC ratios Emissions policies must consider how Hg stream transport is mediated by soils